Nutrient-use efficiency of tectona grandis (Linn. f.) seedlings on basement complex and ferric luvisol soils of Ibadan, Nigeria (2011)
The study investigated the use-efficiency of selected soil nutrient elements - Nitrogen (N), Phosphorus (P) and Potassium (K) in the synthesis of dry matter by Tectona grandis (Linn.f.) seedlings. T. grandis seedlings were grown on basement complex and ferric luvisol soils for 77 days after transplanting (DAT). Sixty polythene pots were filled with each soil type. Sixty soil seedling samples formed an experimental unit that was replicated three times making a total of 360 seedlings. Eight seedlings were selected at intervals of 7 days for the first 28 DAT and four seedlings for the remaining 42 DAT in each experimental unit. Composite samples of soil media and seedlings were taken at intervals of 7 days and chemically analyzed. The dried shoot and leaves were combusted at 500oC, for carbon content determination. Range of daily light intensity during the experiment was 3.5 to 6.2 Klux while daily mean temperature was 24.7 to 27.5oC. Total carbon and biomass results showed that photosynthetic efficiency and photosynthetic carbon production of seedlings grown on basement complex were not significantly different from those of ferric luvisol. It is concluded that an increase in biomass could not be a major indicator of an increase in biomass carbon production. Therefore, photosynthetic efficiency alone may not be an adequate indicator of efficient photosynthetic carbon fixation. The root/shoot ratio was higher than 1.0 in both soils, indicating higher biomass allocations to the roots of the seedling. The study provides basis for the estimation of the phosphorus and nitrogen-supplying power of ferric luvisol and basement complex soils,